2017
DOI: 10.1038/s41598-017-13790-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Behavioral and Neural Responses to Unfairness Under Social Pressure

Abstract: Numerous studies have revealed the key role of social pressure on individuals’ decision-making processes. However, the impact of social pressure on unfairness-related decision-making processes remains unclear. In the present study, we investigated how social pressure modulated men’s and women’s responses in an ultimatum game. Twenty women and eighteen men played the ultimatum game as responders in the scanner, where fair and unfair offers were tendered by proposers acting alone (low pressure) or by proposers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…The increased activation of pgACC was revealed during receiving unfair offers in the social support condition. Similar result has also been found in another study of our group which focused on the impact of social pressure ( Zheng L. et al, 2017 ). The pgACC has been thought to be engaged in person perception and mentalizing ( Amodio and Frith, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…The increased activation of pgACC was revealed during receiving unfair offers in the social support condition. Similar result has also been found in another study of our group which focused on the impact of social pressure ( Zheng L. et al, 2017 ). The pgACC has been thought to be engaged in person perception and mentalizing ( Amodio and Frith, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with Kromer and Bahçekapili (2010), who showed that male participants were more willing to pay money to punish the dictator who had made unfair allocations as an altruistic punishment behavior of the third party. Moreover, this finding is similar to that of Zheng et al (2017), who found that males reject more unfair offers in the high‐ versus low‐pressure context, whereas women accept more unfair offers when facing high social pressure in an ultimatum game. Thus, man and women have different inequity perceptions when individuals behave unfairly, and men may be more likely than women to punish norm‐violating behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that male participants were more willing to pay money to punish the dictator who made unfair allocations. Another study investigated how social pressure modulated men's and women's responses in an ultimatum game (Zheng et al, 2017). The results showed that men rejected more unfair offers in the high‐ versus low‐pressure context, while women accepted more unfair offers when facing high social pressure.…”
mentioning
confidence: 99%
“…As such, single-sex studies have more power to detect a given effect. However, it is important to note that previous studies have found gender differences in the UG 55 , 56 . While the psilocybin response does not appear to be moderated by gender 57 , gender differences in the subjective effects of MDMA have been reported 58 .…”
Section: Discussionmentioning
confidence: 92%